The Implementation of Cooperative Learning Model Type Jigsaw to Improve Student Learning Activities in Class XI IPA 3 SMA Negeri 5 Kendari - Haya, La (Universitas Sembilanbelas November Kolaka, 2023)
Education is not only measured by theoretical knowledge, but also by practical abilities and interpersonal skills. The low level of student learning activity reflects a mismatch between conventional teaching methods and students' actual needs in developing competencies. This study aims to increase student learning activities in biology class XI IPA 3 SMA Negeri 5 Kendari by applying the Jigsaw cooperative learning model. This research was conducted in the second semester of the 2013/2014 academic year. The type of research used is classroom action research (PTK) Kemmis and Taggart with three learning cycles. Each cycle goes through four stages: (1) planning; (2) carrying out actions; (3) observation and (4) reflection. The source of this research data is the measurement of observation sheets in Cycle I, Cycle II, and Cycle III. The data obtained were analyzed using descriptive analysis. From the observations, it was obtained that student learning activities in cycle I with an average student learning activity in cycle I was 3.31 with a percentage of 82.74%, in cycle II it was 3.48 with a percentage of 86.90%, in cycle III with 3.68 with a percentage of 91.96%. It can be concluded that the application of the Jigsaw cooperative learning model can increase student learning activities in biology class XI IPA 3 SMA Negeri 5 KendariÂ Keywords: Learning Activities, JigsawÂ